Vitamin D receptor activation and downregulation of renin-angiotensin system attenuate morphine-induced T cell apoptosis - Chandel, Nirupama (American Physiological Society, 2012)
Opiates have been reported to induce T cell loss. We evaluated the role of vitamin D receptor (VDR) and the activation of the renin-angiotensin system (RAS) in morphine-induced T cell loss. Morphine-treated human T cells displayed downregulation of VDR and the activation of the RAS. On the other hand, a VDR agonist (EB1089) enhanced T cell VDR expression both under basal and morphine-stimulated states. Since T cells with silenced VDR displayed the activation of the RAS, whereas activation of the VDR was associated with downregulation of the RAS, it appears that morphine-induced T cell RAS activation was dependent on the VDR status. Morphine enhanced reactive oxygen species (ROS) generation in a dose-dependent manner. Naltrexone (an opiate receptor antagonist) inhibited morphine-induced ROS generation and thus, suggested the role of opiate receptors in T cell ROS generation. The activation of VDR as well as blockade of ANG II (by losartan, an AT(1) receptor blocker) also inhibited morphine-induced T cell ROS generation. Morphine not only induced double-strand breaks (DSBs) in T cells but also attenuated DNA repair response, whereas activation of VDR not only inhibited morphine-induced DSBs but also enhanced DNA repair. Morphine promoted T cell apoptosis; however, this effect of morphine was inhibited by blockade of opiate receptors, activation of the VDR, and blockade of the RAS. These findings indicate that morphine-induced T cell apoptosis is mediated through ROS generation in response to morphine-induced downregulation of VDR and associated activation of the RAS.